Short- and Mid-Term Changes in Lung Function after Bilateral Pulmonary Metastasectomy - Welter, Stefan; Cheufou, Danjouma; Zahin, Mahmood; Kampe, Sandra; Darwiche, Kaid; Weinreich, Gerhard; Stamatis, Georgios (The Thoracic and Cardiovascular Surgeon, 2016)
Introduction The resection of pulmonary metastases is associated with a loss of lung function. The amount of functional impairment after bilateral metastasectomy remains unclear. Because only around 35% of those patients may expect long-term survival, it is important to preserve enough pulmonary function for an adequate quality of life. This analysis of 31 bilaterally operated patients was performed to describe the amount of pulmonary function loss.Methods This is a post-hoc subanalysis and comparison of a population that was published before. All pulmonary metastasectomies were performed through an anteroaxillary thoracotomy in all patients. Resections were performed with staplers, electrocautery, or laser. All patients had pulmonary function tests (PFTs) preoperative and after 3 months at the follow-up visit, including spirometry, diffusing capacity of lung for carbon monoxide (Dlco) and blood gases. Of the 31 bilaterally operated cases, 15 had additional PFTs after each staged operation before discharge from hospital.Results Altogether, 271 nodules (median 7, mean 8.2) were removed from the 31 patients with a lobectomy in 2, a segmentectomy in 8, and multiple wedge resections in 21 patients, with this being the largest resection. The mean loss of pulmonary function at follow-up visit was forced vital capacity (FVC) − 15.2%, total lung capacity (TLC) − 13.8%, forced expiratory volume in 1 second (FEV1) − 16.3%, and Dlco − 10.3%, all of which were significant (p = < 0.001). The 15 patients with PFTs after each operation showed a stepwise decrease of volume parameters and Dlco with deepest values after the second surgery of around − -40% from preoperative values. At this time, Po2 was also significantly reduced by 10 mm Hg (p = 0.01). Comparing the bilateral group with 86 patients after unilateral metastasectomy, we found significantly more nodules removed in the bilateral group (8.2 vs. 3.1; p < 0.001) and that the loss of volume parameters was twice that of the unilateral group after metastasectomy. Dlco impairment did not differ between the groups (− 10.3 vs. − 9.5%; p = 0.868) after 3 months.Conclusion Midterm pulmonary function impairment after bilateral pulmonary metastasectomy is 15% of spirometry values and 10% of Dlco. Reduction of spirometry values is almost twice compared with the group after unilateral surgery. Early functional loss after the second intervention causes FVC, TLC, and FEV1 reduction of around 40% and is associated with lower Po2 (− 10 mm Hg). Therefore, bilateral metastasectomy can be offered to patients who do not have greater pulmonary limitations.
Keywords: metastasectomy; lung function; bilateral metastasectomy; functional impairment